2022
DOI: 10.3390/microorganisms10061225
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Screening of Antimicrobial Resistance Genes in Gram-Negative Seafood Bacteria

Abstract: From a global view of antimicrobial resistance over different sectors, seafood and the marine environment are often considered as potential reservoirs of antimicrobial resistance genes (ARGs) and mobile genetic elements (MGEs); however, there are few studies and sparse results on this sector. This study aims to provide new data and insights regarding the content of resistance markers in various seafood samples and sources, and therefore the potential exposure to humans in a global One Health approach. An innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…They found isolates of S. algae resistant to β-lactams ( blaOXA-55-LIKE, ampC ), tetracyclines ( tetR, tet34 , and tet35 ), fluoroquinolones ( qnrA3, qnrA7, mepAB —multi-drug efflux pump, mfpA—qnr homolog, emrD - multi-drug efflux pump, and mtdN —multi-drug resistance protein), polymyxin ( eptA ), chloramphenicol ( cat ). Also, Delannoy et al (2022) found Shewanella spp. ( S. indica, S, haliotis, S. algae , and unidentified Shewanella spp.)…”
Section: The Most Popular Gram-negative Pathogenic Bacteria In Molluscsmentioning
confidence: 98%
See 2 more Smart Citations
“…They found isolates of S. algae resistant to β-lactams ( blaOXA-55-LIKE, ampC ), tetracyclines ( tetR, tet34 , and tet35 ), fluoroquinolones ( qnrA3, qnrA7, mepAB —multi-drug efflux pump, mfpA—qnr homolog, emrD - multi-drug efflux pump, and mtdN —multi-drug resistance protein), polymyxin ( eptA ), chloramphenicol ( cat ). Also, Delannoy et al (2022) found Shewanella spp. ( S. indica, S, haliotis, S. algae , and unidentified Shewanella spp.)…”
Section: The Most Popular Gram-negative Pathogenic Bacteria In Molluscsmentioning
confidence: 98%
“…Although global seafood production is growing yearly, systematic surveillance of AMR in this sector is mainly lacking or has only been at a pilot study level. One main reason for this gap is the difficulties of investigating AMR phenotypes of marine bacteria, which often have specific growth requirements, and often lack standardized antimicrobial susceptibility testing methods and interpretation criteria ( Delannoy et al, 2022 ). Among the most frequently found bacteria in bivalve molluscs are those belonging to the Proteobacteria phylum ( Pierce and Ward, 2019 ).…”
Section: Anthropogenic Impact On Marine Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors, based on the biomolecular ARG trades between food matrices and human microbiota, performed PCR assays, amplifying numerous genetic determinants from many bacterial species isolated in fresh fillets (fish and mammalian species). Molecular tests were designed to discover nucleotide sequences, which codify resistance against the most frequently administrated antibiotic molecules in veterinary and human medicine (i.e., tetracyclines, beta-lactams, and quinolones) [ 10 , 11 , 12 , 13 ]. They discovered the phenotypic expression of many antibiotic resistance patterns against the veterinary legally permitted molecules and the so-called Critical Important Antimicrobials (CIA), whose usage is strongly indicated for humans only [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…isolated from retail seafood revealed that 98% of the tested isolates were resistant to three or more antibiotics [ 18 ]. However, in general, the occurrence of antimicrobial-resistant bacteria in seafood isolates decreases with increasing distance from possible sources of fecal contamination [ 19 ].…”
Section: Introductionmentioning
confidence: 99%